A study of the effect of palm oil as MQL lubricant on high speed drilling of titanium alloys - Rahim, E. A.; Sasahara, H (ScienceDirect, 2011)
The main objective was to study the potency of MQL palm oil (MQLPO) as a lubricant in the high speed drilling of Ti–6Al–4V. For the comparison, MQL synthetic ester (MQLSE), air blow and flood conditions were selected. Uniform flank wear, micro-chipping, thermal cracking and flaking were the dominant tool failure modes. It was found that MQLSE and MQLPO gave comparable performance with the flood conditions. In addition, MQLPO outperformed MQLSE on the cutting forces, temperature, power and specific cutting energy. This shows that palm oil can be used as a viable alternative to synthetic ester for MQL lubricant.